A study on anti-doping law in Malaysia / Muhammad Syamil Hillmy, Wan Naimah Zulkhefli and Wan Nur Fariha Ramlan - Hillmy, Muhammad Syamil; Zulkhefli, Wan Naimah; Ramlan, Nur Fariha (Faculty of Law, 2012)
This research is about anti-doping law in Malaysia. The main objective is to examine various types of existing anti-doping law, rules, policy and international conventions around the world in order to provide a comprehensive law to govern doping problems in Malaysia. An emphasis on the Australian anti-doping law is made for it provides one of the best and holistic legal frameworks in anti-doping. Furthermore, the current situation relating to sports law in Malaysia is being discussed. The lack of laws to govern the local sports industry has been highlighted together with several law principles such as judicial review and natural justice in sports adjudication. Apart from that, the implementation of various regulatory mechanisms such as internal tribunals has been scrutinized. The effectiveness, advantages and disadvantages of the current practice will be examined followed by appropriate suggestions and recommendations necessary for the government to improve the sports law in Malaysia particularly on doping problems.